Ecology, soils, and the left : an eco-social approach - Mauro, Salvatore Engel-Di; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Soil degradation is real and global, even if the evidence is not so easy to glean. Degradation poses comparable risks to greenhouse gas emissions, deforestation, and nonhuman animal extinctions. Few have noticed soil degradation as the problem it has become, except most indigenous peoples in their struggles for survival.
Keywords: Environment; Political science; Political theory; World politics; Political philosophy; Environmental policy; Environment; Environmental Politics; Political Science; Political Theory; Political Philosophy; Political History